Amaranth and buckwheat grains: Nutritional profile, development of functional foods, their pre-clinical cum clinical aspects and enrichment in feed - Kumar, Harsh; Guleria, Shivani; Kimta, Neetika; Dhalaria, Rajni; Nepovimova, Eugenie; Dhanjal, Daljeet Singh; Alomar, Suliman Y; Kuca, Kamil (Current research in food science, 2024)
The resurgence of interest in amaranth and buckwheat as nutrient-rich and versatile grains has incited extensive research aimed at exploring their potential benefits for sustainable agriculture and human nutrition. Amaranth is renowned for its gluten-free nature and exceptional nutritional profile, offering high-quality proteins, fiber, minerals, and bioactive compounds. Similarly, buckwheat is recognized for its functional and nutraceutical properties, offering a plethora of health benefits attributed to its diverse array of biologically active constituents; flavonoids, phytosterols, and antioxidants. This comprehensive review comprehends the existing understanding of the composition, anti-nutritional factors, biological activity, and potential application of these grains, emphasizing their pivotal role in addressing global food insecurity. Developed functional foods using these grains are having enhanced physicochemical properties, mineral content, phenolic content and overall sensory acceptability. In addition, the consumption of developed functional food products proved their health benefits against various type of anomalies. Moreover, enrichment of both grains in the animal feeds also showing positive health benefits.
Keywords: Pseudocereal grains; Food insecurity; Bioactive compounds; Health benefits; Product development